Redox properties of serum albumin - Anraku, M.; Chuang, Victor; Maruyama, T.; Otagiri, M. (Elsevier BV, 2013)
Background: Oxidative damage results in protein modification, and is observed in numerous diseases. Human serum albumin (HSA), the most abundant circulating protein in the plasma, exerts important antioxidant activities against oxidative damage. Scope of Review: The present review focuses on the characterization of chemical changes in HSA that are induced by oxidative damage, their relevance to human pathology and the most recent advances in clinical applications. Major Conclusions: The antioxidant properties of HSA are largely dependent on Cys34 and its contribution to the maintenance of intravascular homeostasis, including protecting the vascular endothelium under disease conditions related to oxidative stress. Recent studies also evaluated the susceptibility of other important amino acid residues to free radicals. The findings suggest that a redox change in HSA is related to the oxidation of several amino acid residues by different oxidants. Further, Cys34 adducts, such as S-nitrosylated and S-guanylated forms also play an important role in clinical applications. On the other hand, the ratio of the oxidized form to the normal form of albumin (HMA/HNA), which is a function of the redox states of Cys34, could serve as a useful marker for evaluating systemic redox states, which would be useful for the evaluation of disease progression and therapeutic efficacy. General Significance: This review provides new insights into our current understanding of the mechanism of HSA oxidation, based on in vitro and in vivo studies.